2020
DOI: 10.28991/cej-2020-03091492
|View full text |Cite
|
Sign up to set email alerts
|

Study a Structural Behavior of Eccentrically Loaded GFRP Reinforced Columns Made of Geopolymer Concrete

Abstract: This study investigated a modern composite material, which is a short geopolymer concrete column (GPCC) reinforced by GFRP bars. The structural performances of GPCC subjected to eccentric load were studied and compared to the normal strength concrete column (NSCC) reinforced by steel bars. In this study, the primary experimental parameters were the reinforcement bars types, load eccentricity, and concrete types. Seven short columns were tested: three normal strength concrete columns reinforced by steel bars, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Verification of Eq. ( 9) was carried out on test data from Albitar, et al [24], Elchalakani, et al [25], Hussein et al [26], Ganeshan N., et al [8], Sujatha [27], y = 6.8016x -0.186 R² = 0.5617…”
Section: Development Of Compressive Strength Model For Confined Geopo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Verification of Eq. ( 9) was carried out on test data from Albitar, et al [24], Elchalakani, et al [25], Hussein et al [26], Ganeshan N., et al [8], Sujatha [27], y = 6.8016x -0.186 R² = 0.5617…”
Section: Development Of Compressive Strength Model For Confined Geopo...mentioning
confidence: 99%
“…Similar results were obtained by Sujatha, et al [12] in a study on a GPC slender column with a circular cross-section. Nhabih, et al [13] studied the structural behavior of eccentrically loaded GFRP reinforced columns made of geopolymer concrete. Seven short square columns were tested.…”
Section: Introductionmentioning
confidence: 99%
“…While the steel jacket also thin steel used as a tube and the concrete-filled this tube inside. Many researchers [31][32][33][34][35][36][37][38][39][40] were used the jacketing by ferrocement and steel jackets which showed that the ferrocement and steel jackets considered a good way to enhance the strength capacity against different load types and improve the RC columns strength. Despite the multiplication of reinforcement methods and the effectiveness of some of them on the general performance of the column, some methods are expensive, such as reinforcement with the use of a steel jacket.…”
Section: Introductionmentioning
confidence: 99%